Store Atmosphere Strategy in Micro, Small, and Medium Enterprises TikTok as a Marketing Strategy Supporter - Setiawan Jodi, I Wayan Gede Antok; Kespandiar, Tengku; Hamzah, Ramadhani; Munizu, Musran; Erna, Erna (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The business world in Indonesia is growing very rapidly, which is indicated by the sharp competition. Understanding consumer behavior is a key skill needed by business actors so that consumers can buy the goods or services they offer. Digital marketing enables micro, small, and medium enterprises to reach wider consumers at a more efficient cost than traditional marketing methods. TikTok supports micro, small, and medium enterprises in various ways, such as through the TikTok Shop feature, partnership programs, and digital training. TikTok Shop allows micro, small, and medium enterprises to sell their products online on the TikTok platform. The purpose of this study is to determine how Micro, Small, and Medium Enterprises on TikTok use the store atmosphere strategy as a marketing strategy supporter. This study uses an observational research type that will help achieve the research objectives. Observational research analysis requires the help of quantitative data, such as books, journals, and mass media articles. The research results show that the atmosphere in TikTok Shop is an e-commerce platform that allows users to shop for products directly within the TikTok application. Users can browse and purchase products from their feed or through the Shop tab.